Effect of Outward and Inward Dimple Located on Different Positions of Aerofoil Section at a Typical Low Reynolds Number - A Aswatha Narayana, P.; K A, Rasya; S Prasad, Spoorthi; ., . (International Journal of Engineering and Technology, 2018)
The main objective of this paper is to investigate the enhancement of the aerodynamic characteristics of NACA 4415 aerofoil section. This enhancement includes introduction of dimple on the aerofoil section which creates vortices and delays the flow separation. The work describes the computational analysis of dimple at different positions for different aspect ratios. This study has been carried out on an aerofoil section for a typical low Reynolds number of 47,000 using CFD tool ANSYS FLUENT. Â Â